Current status of older people with chronic diseases adopting digital health technologies: A scoping review - Li, C.; Wang, H.; Yuan, J.; Shi, L.; Chen, Y.; Gao, Z.; Zhao, L.; Oliveira, A. (Digital Health, 2025)
Background Digital health technologies (DHTs) promise enhanced health for older people, yet the digital divide hinders adoption and utilization. This study aimed to identify DHTs that can help older people in chronic disease management, specifically the facilitators, barriers, needs, and scenarios. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, Scopus, and IEEE for studies published in English between 2000 and 2024. Analysis of included articles included descriptive synthesis and thematic analysis. Results Forty-seven studies were included, yielding 148 DHTs classified as Medical services and support (n = 94) or Self-management (n = 54). Experience of Use and Interpersonal Support were the main facilitators of the use of DHTs. Awareness of Competence, Technological Factors, Sense of Security, and Individual Factors are barriers. Needs can be categorized into Service Functions and Subjective Needs, and the main scenarios include Home, Community, and Hospital. Conclusions Digital health technologies are widely used, especially in developed countries, but challenges remain in developing countries and among specific patient. Future studies should focus on addressing concerns about DHT availability, security, and reliability in older people, actively incorporating feedback, providing personalized service, and fully mobilizing positive social factors to promote DHTs.